Effect of Bearing Compliance on Thermo-hydrodynamic Lubrication of High Speed Misaligned Journal Bearing Lubricated with Bubbly Oil - Abass, Basim Ajeel; Sahib, Murtada Mohammed (Al-Khwarizmi Engineering Journal, 2015)
Abstract In the present work the effect of bearing compliance on the performance of high speed misaligned journal bearing lined with a compliant PTFE liner lubricated with bubbly oil at high speeds has been studied. The effect of induced oil film temperature due to shearing effect has been implemented. Hydrodynamic effect of the complaint bearing and the influence of aerated oil have been examined by the classical thermohydrodynamic lubrication theory modified to include the effect of oil film turbulence and oil film temperature with suitable models for bubbly oil viscosity and density. The effect of liner elastic deformation has been implemented by using Winkler model. The effects of variable density and specific heat on the most importantbearing parameters such as maximum pressure, maximum temperature, bearing load carrying capacity and power losses have been investigated.The results obtained show that the oil film pressure and load carrying capacity increased for the bearing lubricated with bubbly oil of higher aeration level and smaller size of air bubbles. Including the effect of elastic deformation of the bearing liner reduces the oil film pressure, load carrying capacity and frictional power loss for the misaligned bearing working at the same circumstances Keywords: Journal bearings, hydrodynamic lubrication, THD, compliant effect, bubbly oil, misalignment effect.